Red blood cell alterations by in vitro action of Trichinella spiralis newborn larvae - Patricia Ponce de León; Martin Toderi; Horacio Castellini; Bibiana Riquelme (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2020)
Background: T. spiralis establishes an intimate contact with the host erythrocytes during the newborn larvae migration through the bloodstream to their encystment in the muscle.  Objective: In the present work we study the alterations in the mechanical and aggregation properties of red blood cells produced in vitro by newborn larvae at low concentrations (100, 250, 500, and 1000 larvae/mL).  Methods: The study was performed by incubating human erythrocytes with an equal volume of different concentrations of newborn larvae for 30 minutes, with controlled agitation. To evaluate the erythrocyte alterations by the action of the larvae, the Erythrocyte Rheometer, the Optical Chip Aggregometer, and the Digital Image Analysis were used.  Results: In the treated erythrocyte samples, a decrease in isolated cell numbers and an increase in the aggregates were observed respect to the control at the higher larval concentration (1000 larvae/mL). The deformability index, the elastic modulus and surface viscosity showed no significant differences with the control; however, the storage modulus of the erythrocyte membrane decreased significantly with the increase in larval concentration. Erythrocyte aggregation parameters showed that the aggregation index increased with the larvae concentration present in the incubation, highlighting the presence of larger aggregates and clusters. The time to attain half of the maximum aggregation diminished, which implies faster aggregation kinetics.  Conclusion: The results observed in vitro describe the red blood cell alterations that could be produced during in vivo infection in the host.